DNA methylation and human disease - Robertson, Keith D. (Nature reviews. Genetics, 2005)
Key Points DNA methylation is an epigenetic modification of DNA that is important for the normal regulation of transcription, embryonic development, genomic imprinting, genome stability and chromatin structure. DNA methylation is controlled by DNA methyltransferases, methyl-CpG binding proteins and other chromatin-remodelling factors. Aberrations in the DNA methylation system have an important role in human disease. DNA methylation patterns are globally disrupted in cancer, with genome-wide hypomethylation and gene-specific hypermethylation events occurring simultaneously in the same cell. Loss of normal imprinting contributes to several inherited genetic diseases in humans. These diseases include Beckwith–Wiedemann, Prader–Willi, and Angelman syndromes, Albright hereditary osteodystrophy (AHO) and pseudohypoparathyroidism Ia (PHP-Ia) and PHP-Ib, and transient neonatal diabetes. In vitro manipulation of embryos during assisted reproduction procedures might lead to imprinting defects in the offspring. Abnormal expansion of a CGG repeat in the FMR1 gene, accompanied by its hypermethylation and silencing, leads to fragile X syndrome. By contrast, contraction and hypomethylation of a larger 3.3 kb repeat leads to facioscapulohumeral muscular dystrophy. Mutations in the machinery that regulates DNA methylation patterns and chromatin structure also contribute to human disease. Mutations in DNMT3B and ATRX lead to immunodeficiency, centromeric instability and facial anomalies (ICF) syndrome and Alpha-thalassemia/mental retardation syndrome, X-linked syndrome, respectively. Both disorders are characterized by localized disruptions in DNA methylation patterns. The insulator/boundary proteins CCCTC-binding factor and BORIS, and the repression system known as RNAi, are probably involved in establishing and maintaining normal DNA methylation patterns. DNA methylation is a crucial epigenetic modification of the genome that is involved in regulating many cellular processes. These include embryonic development, transcription, chromatin structure, X chromosome inactivation, genomic imprinting and chromosome stability. Consistent with these important roles, a growing number of human diseases have been found to be associated with aberrant DNA methylation. The study of these diseases has provided new and fundamental insights into the roles that DNA methylation and other epigenetic modifications have in development and normal cellular homeostasis.